2015
DOI: 10.1364/boe.6.003149
|View full text |Cite
|
Sign up to set email alerts
|

Optoacoustic detection of tissue glycation

Abstract: Abstract:Oxidative-based diseases including diabetes, chronic renal failure, cardiovascular diseases and neurological disorders are accompanied by accumulation of advanced glycation endproducts (AGE). Therefore, AGE-associated changes in tissue optical properties could yield a viable pathological indicator for disease diagnostics and monitoring. We investigated whether skin glycation could be detected based on absorption changes associated with AGE accumulation using spectral optoacoustic measurements and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 31 publications
(35 reference statements)
0
16
0
Order By: Relevance
“…The conditions of physiological hyperglycemia were provided by immersion of porcine skin samples in the ribose solution during 17 days. As a result, the increase of the optoacoustic signal with the incubation time and the maximal absorption of light by the glycated skin in the wavelength range 540-620 nm was observed [157]. Possibly, the increased intensity of the optoacoustic signal with the growth of skin glycation degree is related not only to the high light absorption by glycated skin (in the wavelength range 540-620 nm), but also to the increased efficiency of light-to-sound conversion due to greater tissue elasticity because of the crosslinks between the fibres.…”
Section: Skinmentioning
confidence: 95%
See 2 more Smart Citations
“…The conditions of physiological hyperglycemia were provided by immersion of porcine skin samples in the ribose solution during 17 days. As a result, the increase of the optoacoustic signal with the incubation time and the maximal absorption of light by the glycated skin in the wavelength range 540-620 nm was observed [157]. Possibly, the increased intensity of the optoacoustic signal with the growth of skin glycation degree is related not only to the high light absorption by glycated skin (in the wavelength range 540-620 nm), but also to the increased efficiency of light-to-sound conversion due to greater tissue elasticity because of the crosslinks between the fibres.…”
Section: Skinmentioning
confidence: 95%
“…Based on the studies of the fluorescence properties of the advanced glycation end products of hemoglobin, skin, cornea, aorta, articular tendon [34,36,116,118,119,124,157], and the corresponding changes in the nonlinear susceptibility of the tissue structures [34,123,158], it was found that the glycation facilitates the increase of the tissue fluorescence intensity [34,116,118,119,124,125,157] and the decrease of the second harmonic generation intensity [34,123,158] (Fig. 4).…”
Section: Different Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…AGEs are predictors of disease-associated with long-term complications, thus their early non-invasive detection is of paramount importance. Spectral optoacoustic measurements of AGE in a porcine skin model demonstrated promising prospects for the detection and quantification of AGE accumulation [327]. Optoacoustic monitoring of stroke progression in the whole brain of living mice in a model of middle cerebral artery occlusion (MCAO) was also suggested [299].…”
Section: Applications Enabled By Optoacoustic Visualization Of Multmentioning
confidence: 99%
“…Nevertheless, similarly to optical methods, optoacoustic sensing is limited by water absorption at longer wavelengths. Water contributes minimally to optoacoustic measurements in the visible range (450-650 nm) and nearinfrared range (650-900 nm) [14], but it contributes strongly to measurements at wavelengths longer than 900 nm, limiting the sensitivity of the technique for detecting proteins, lipids, collagen and sugars [14], [26], [27].…”
Section: Introductionmentioning
confidence: 99%